Evaluation Of Implementation Of MBKM: Does Academic Stress Affect On Student Learning Outcomes? - Hakim, Adi Lukman; Fajri, Mega Barokatul; Faizah, Erna Nur (International Journal of Educational Research & Social Sciences, 2022)
Stress is a psychological symptom that we often encounter in everyday life, where every individual must have experienced it. Students as a milestone in the success of a nation are required to be able to adapt to the environment quickly. This study aims to determine whether there is academic stress on student learning outcomes at the University of Muhammadiyah Lamongan, Faculty of Economics and Business, Management Study Program. This type of research is observational with a crosssectional design. The population in this study were all students of the 2019/2020 and 2020/2021 Management Study Programs with a total population of 173 people. The sampling technique used was total sampling from the population. The method of data collection was done by distributing questionnaires to respondents. Furthermore, statistical tests were carried out using the chi square test with 0.05. Based on the research results show that; 1) stressors from academic stress Management study program students in semester 5 and 3 have high gains. This means that students feel that MBKM's academic activities make them feel stressed. More specifically, the greatest stressor is caused by pressure from learning and self-expectations that are not met, 2) Student learning outcomes in the implementation of the independent learning curriculum are included in the sufficient category. That is, cognitive competence or knowledge, affective or feeling, and psychomotor or skills obtained from MBKM are not too high or not too low. 3) The relationship between academic stress and student learning outcomes is positive and significant. It means. the higher the degree of student academic stress, the lower the learning outcomes, and vice versa, and 4) the implementation of MBKM from the student's point of view has a good impact on their self-development. However, in order for the implementation to take place optimally, students, lecturers, and stakeholders can work together in preparing to participate in the next MBKM, such as formulating the implementation of the MBKM more clearly and carefully, as well as equipping students with the skills to learn independently.